Mit Digitalisierung zu klimaneutralem Wachstum und Wohlstand - Vera Demary; Thilo Schaefer (Wirtschaftsdienst, 2023)
– Germany's growth and prosperity face multiple challenges from climate change and demographic shifts. Active policy meas-ures and digitalisation have the potential to alleviate these problems and promote climate-friendly innovations. However, the transfor-mation requires significant investments and infrastructure development. Unclear framework conditions and a lack of skilled IT expertshinder progress. To achieve digital green growth, Germany needs a mix of technological innovations, robust infrastructure and regula-tory support. Making these challenges a high political priority will enable sustainable growth and prosperity in the face of the ongoingstructural transformation.
Keywords: L52; O33; Q58; 330